KANDUNGAN KLOROFIL, FIKOERITRIN DAN KARAGINAN PADA RUMPUT LAUT Eucheuma spinosum YANG DITANAM PADA KEDALAMAN YANG BERBEDA - Veronika, Veronika; Izzati, Munifatul (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2009)
Research on effect Eucheuma spinosum depth on chlorophyll, phycoerythrin and carageenan content has been done. The research was conducted at Awur bay, Jepara. Using bamboo racks, Eucheuma spinossum was planted at difference depth, approximately 10 seed were planted. Data on content of chlorophyll a, phycoerythrin and carageenan were monitored. The collecting data was analyzed by Anova, followed by Duncan test. Result indicated that, chlorophyll increased by increasing of Eucheuma depth. The highest content of carageenan was resulted bu Eucheuma that planted at adepth of 70 cm, the difference of pigment and carageenan content was determined by the quality of sun light.